Question
upstudy study bank question image url

Solve for \( y \) : \[ (3 y+10)^{2}-64=0 \] INSTRUCTION: Where appropriate, give you answer as a simplified fraction.

Ask by Gross Schofield. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( y = -6 \) or \( y = -\frac{2}{3} \)

Solution

Solve the equation \( (3y+10)^{2}-64=0 \). Solve the quadratic equation by following steps: - step0: Solve using square roots: \(\left(3y+10\right)^{2}-64=0\) - step1: Add or subtract both sides: \(\left(3y+10\right)^{2}=64\) - step2: Simplify the expression: \(3y+10=\pm \sqrt{64}\) - step3: Simplify the expression: \(3y+10=\pm 8\) - step4: Separate into possible cases: \(\begin{align}&3y+10=8\\&3y+10=-8\end{align}\) - step5: Solve the equation: \(\begin{align}&y=-\frac{2}{3}\\&y=-6\end{align}\) - step6: Rewrite: \(y_{1}=-6,y_{2}=-\frac{2}{3}\) The solutions to the equation \((3y+10)^{2}-64=0\) are \(y=-6\) and \(y=-\frac{2}{3}\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve for \( y \) in the equation \( (3y + 10)^{2} - 64 = 0 \), we first add 64 to both sides: \[ (3y + 10)^{2} = 64 \] Next, we take the square root of both sides: \[ 3y + 10 = \pm 8 \] Now, we split this into two separate equations: 1. \( 3y + 10 = 8 \) 2. \( 3y + 10 = -8 \) For the first equation, we subtract 10 from both sides: \[ 3y = 8 - 10 \] \[ 3y = -2 \] Dividing by 3 gives: \[ y = -\frac{2}{3} \] For the second equation, we also subtract 10 from both sides: \[ 3y = -8 - 10 \] \[ 3y = -18 \] Dividing by 3 gives: \[ y = -6 \] Thus, the solutions are: \[ y = -\frac{2}{3} \quad \text{and} \quad y = -6 \]

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy